Evaluasi Kebijakan Tentang Perlindungan Pekerja Migran Indonesia di Provinsi Jawa Timur - Anita Evilia; Indah Murti; Supri Hartono (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to identify and analyze the evaluation of policies concerning the protection of Indonesian Migrant Workers (PMI) in East Java Province. The research employs William N. Dunn’s policy evaluation theory, which consists of five key indicators: effectiveness, efficiency, adequacy, equity, and responsiveness. A descriptive qualitative approach was used in this study, with data collected through observation, interviews, and documentation techniques. The data were analyzed through several stages, including data collection, data reduction, data presentation, and conclusion drawing. The findings indicate that the implementation of the Indonesian Migrant Worker Protection Policy at the UPT P2TK of East Java Province has generally been successful and has achieved positive outcomes. These achievements can be seen in terms of policy effectiveness in reaching its objectives, efficiency in utilizing available resources, adequacy of services provided to migrant workers, equitable access to protection services, and responsiveness to the needs and concerns of migrant workers. Nevertheless, several technical challenges remain and require further improvement, including the integration of One-Stop Integrated Service Centers (LTSA), the readiness of protection facilities, and the enhancement of rapid response mechanisms. Therefore, efforts are needed to strengthen service digitalization, expand village-based outreach programs, increase human resources capacity, develop migrant worker empowerment programs, strengthen international cooperation, optimize shelter services, and conduct regular policy evaluations to improve the quality and sustainability of migrant worker protection in East Java.